Ultrastructure of the urethra of the Mongolian gerbil - Pinheiro, PFF; Almeida, CCD; Segatelli, T. M.; Martinez, M.; Padovani, C. R.; Martinez, F. E. (Springer, 2002)
Objective: the urethra is the main port of entry of sexually transmitted pathogens. However, papers on the morphology of the urethra are scarce. The Mongolian gerbil is a rodent native of the Mongolia and China and has been utilized as a laboratory animal since the 1960s. This work describes the ultrastructure of the urethra of the Mongolian gerbil to provide data for future experimental studies. Methods: the urethra of ten adult male gerbils was studied by transmission electron microscopy. Results: the epithelium of the pelvic urethra possesses two cell types: I and II, without the formation of cellular layers, while the penile urethra possesses cellular layers: basal, intermediate and superficial. The urethra presents neurosecretory cells belonging to the amine precursor uptake and decarboxylation system. Conclusions: the urethral epithelium of the gerbil is a neurosecretory epithelium, part of the amine precursor uptake and decarboxylation system.
Keywords: urethra; neurosecretory cell; electron microscopy; rodents; gerbil